Analisa Head Losses dengan Penerapan Simulasi pada Diameter Pipa dan Pengaruh Nilai Net Positive Suction Head terhadap Terbentuknya Kavitasi pada Pompa - Siti Aisyah; Zulham Effendi; Wahyu Yoga Pratama (PERTETA, 2021)
The pump works by converting mechanical energy into kinetic energy where along the fluid flow there will be a flow loss which causes a decrease in the thrust pressure on the discharge side of the pump. This is due to fluid friction against the pipe walls, and the use of elbows, valves, etc. This analysis aims to calculate the amount of pressure loss (head losses) in the cross-sectional area of ​​the pipe, the available Nett Positive Suction Head (NPSHa), and in the end it will be compared with the required Nett Positive Suction Head (NPSHr) of the pump. This research was conducted in one of the Palm Oil Mill in Tanah Putih District, Rokan Hilir Regency, Riau Province. Data obtained from pump specification data, suction pipe specifications, pressure pipe specifications, daerator height data, upper drum height data, and pumped water temperature data. The instrument analyzed is a pump engine that distributes water from the daerator to the upper drum with the Pump Brand : Southern Cross, type: 52L-4, pump capacity: 25 m3/hour, pump rotation : 3000 rpm, head : 40 meters, temperature : 100 0C, year : 1989. The results obtained that the flow velocity in the suction and compressive pipes is 0.8567 m⁄s, the Reynold number for pipe 4